An experimental and numerical investigation of RC slabs externally strengthened by perforated steel plates. (November 2022) - Sahranavard, Saeed; Jahangir, Hashem; Haji Kazemi, Hasan
Abstract: In this paper, the flexural behavior of two-way reinforced concrete (RC) slabs externally strengthened by perforated steel plates was studied. The thickness of the strengthening plates, arrangement of perforated holes, area of the opening in the strengthening plate and the type of connection to the RC slab, including expansion bolts and epoxy resins, were investigated as the most important parameters. To achieve this goal, eight two-way RC slab specimens with 1200 mm × 1200 mm × 80 mm dimensions were constructed and strengthened by 900 mm × 900 mm steel plates. The flexural behavior of the specimens was tested while applying a semi-concentrated load at their center. The load–displacement curves, elastic stiffness, load-bearing capacities, ductility ratios, and fracture energies of the specimens were analyzed and compared. To further investigate the flexural behavior of two-way RC slabs, the numerical models of all the experimental specimens constructed in ABAQUS software and the von Mises stress contours were obtained. The results show that the most increase in load-bearing capacities was obtained in non-perforated strengthening plates with 1 and 2 mm thickness with 202 and 134 % with respect to the control specimen. Using just expansion bolts as the connection system most influences the ductility ratio increment equal to 220 %. Among different geometrical arrangements of the holes, the circular perforation increased the fracture energy by 253 % compared to the control specimen. Moreover, the resulting von Mises stress contours of numerical models remarkably agreed with obtained experimental results from the strengthened two-way RC slabs.